(untitled) (Sustainability in Debate, 2020)
Over the known history of Brazilian sertões migration has been recorded as a human response to drought episodes. Social protection policies beginning around 2003 had dramatically diminished poverty rates and, within this context, migration changed compared to other periods, becoming more heterogeneous and diffuse. The article aims to explore the link between drought, migration and social protection in the Brazilian semiarid region based upon the analysis and conceptual discussion about two case studies: Submédio São Francisco and Seridó Potiguar. In contrast with the past, actual migration holds an indirect relation to climate. Public policy softened the impacts of the climate over livelihoods and changed the coping strategies. In this sense, mobility outside the semi-arid was not a strategy to survive. Yet, the role of the state in the preceding decades and the region’s historical path ”“ inseparable from its climate ”“ drew persistent migration flows that still reverberate in present dynamics. Â